1997
DOI: 10.2323/jgam.43.209
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of multicopy suppressor genes that complement a defect in the Wis1-Sty1 MAP kinase cascade involved in stress responses in Schizosaccharomyces pombe.

Abstract: The Wis1-Sty1 mitogen-activated protein (MAP) kinase cascade is one of the major signaling systems involved in a wide range of stress responses in Schizosaccharomyces pombe. It is known that dwisl and dstyl mutants exhibit highly pleiotropic phenotypes, including a phenotype of temperature sensitivity for growth. In this study, we screened multicopy suppressor genes that allow both the dwisl and dstyl mutants to grow simultaneously at a non-permissive temperature, 37°C. Two such multicopy suppressors were clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…First, we analyzed the suppressing ability of some plasmid clones in our laboratory stock to determine whether they could improve the reduced viability of the Dsty1 mutant. Previously we screened an S. pombe genomic library for a plasmid that could suppress the heat-stress sensitivity of the Dsty1 mutant (Yamada et al, 1997). Among the suppressing plasmids, pSDS23, which encodes protein that functions as a multicopy suppressor for mutations of the PP1 protein phosphatase and the 20S cyclosome/anaphase-promoting complex (APC), and pHXK2, which encodes hexokinase 2, were revealed not to suppress the short-lived phenotype of the Dsty1 mutant (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we analyzed the suppressing ability of some plasmid clones in our laboratory stock to determine whether they could improve the reduced viability of the Dsty1 mutant. Previously we screened an S. pombe genomic library for a plasmid that could suppress the heat-stress sensitivity of the Dsty1 mutant (Yamada et al, 1997). Among the suppressing plasmids, pSDS23, which encodes protein that functions as a multicopy suppressor for mutations of the PP1 protein phosphatase and the 20S cyclosome/anaphase-promoting complex (APC), and pHXK2, which encodes hexokinase 2, were revealed not to suppress the short-lived phenotype of the Dsty1 mutant (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In brief, the 1.34-kb DNA fragment shown in Fig. 2 was cloned in the vector plasmid pLDblet (Yamada et al, 1997). To introduce a stop codon into Ecl1 protein, site-directed mutagenesis was performed on the pSht3 plasmid using the site-directed mutagenesis primer: CTGCCATCCTAAGTGGTGGCT.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Escherichia coli -S. pombe shuttle vector pLBDblet (Yamada et al 1997) is a plasmid constructed by replacing the ura4 gene in the plasmid pDblet (Brun et al 1995) with Saccharomyces cerevisiae LEU2 gene. Plasmid pMN903 is a pLBDblet derivative that harbors 3.5 kb of HindIII fragment containing the catalase gene of S. pombe.…”
Section: Plasmidmentioning
confidence: 99%
“…During the course of our studies on the osmotic response in S. pombe (Aiba et al 1995;Ohmiya et al 1995Ohmiya et al , 1997Yamada et al 1997), we found that an atf1D mutant exhibits a novel phenotype: it shows an apparent hypersensitivity to calcium. In this study, we attempted to clarify this particular phenotype, with special reference to the MAPK signaling pathway discussed above.…”
Section: Introductionmentioning
confidence: 98%